Implementing smartphone enabled collaborative travel: Routes to success in the tourism domain. (February 2017) - Dickinson, Janet E.; Hibbert, Julia F.; Filimonau, Viachaslau; Cherrett, Tom; Davies, Nigel; Norgate, Sarah; Speed, Chris; Winstanley, Chris
Abstract: Smartphone technology can help identify current and anticipate future patterns of behaviour and, with its social networking capabilities, allow users to imagine and organise collaborative travel opportunities, such as lift share. This has led to the development of collaborative apps designed to enable activities like lift sharing. Such apps require new norms of behaviour to establish a user base and research has yet to address the socio-cultural barriers to both the use of this technology to organise travel and the sharing of personal space that collaborative travel entails. This paper reports the findings of a study which designed, built and tested a collaborative travel app in the tourism domain. Data derived from exploratory interviews, post-trial interviews and a questionnaire reveal that user age and extent of mobile engagement play a less significant role than expected, while other aspects of the social exchange, notably social tie strength, trust and obligations play a more marked role. A conceptual framework and discussion of strategies to address these barriers provides insight into appropriate contexts and routes for implementation of collaborative travel apps. Highlights: Smartphone technology can help identify lift share opportunities. A collaborative travel app was designed, built and tested in the tourism domain. Social tie strength, trust and social obligations play an important role in uptake. Norms for use need to be established based around existing social groups.